Syro-Palestinian stamp seals from the Persian Period (538-332 B.C.): an analysis of their iconographic motifs and inscriptions - Klingbeil, Martin Gerhard (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Ancient Studies)--University of Stellenbosch, 1992.